Meningkatkan Hasil Belajar PAK Melalui Model PBL pada Fase B Kelas IV SDN 13 Terepong - Maria Gumala; Dicky Aprianto; Hedwigis Dian Permatasari (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education of fourth grade students of SDN 13 Terepong through the application of problem-based learning (PBL) model. Based on initial data, only 30% of students met the criteria for achieving learning objectives, while the remaining 70% were still below the threshold. The learning model that has been used is teacher-centered, less varied, and the limited facilities and skills of teachers in using technology contribute to low student involvement in learning. PBL was chosen as a solution because it involves students actively in solving problems, improving critical thinking skills, collaboration, and connecting subject matter with everyday life. This classroom action research was conducted in two cycles. In the first cycle, only 30% of students reached the category of “Proficient, 50% proficient, 20% decent and 0% just developing. “Through more intensive guidance, in the second cycle, there was an increase where 50% of students reached the category of “Proficient and Proficient”. The results of this study indicate that the application of PBL can improve student learning outcomes in cognitive, affective, and psychomotor aspects. Students are more actively involved in the learning process, showing improvement in concept understanding, critical thinking skills, and collaboration. Therefore, PBL proved to be an effective method to improve the quality of PAK learning at SDN 13 Terepong, especially on the material “I am a Unique Person.”